IngenierÃa Del Conocimiento Aplicada Al Estudio De PercepciÃ³n Del Turismo Utilizando OntologÃas OWL Derivadas De Un LÃ©xico Extendido Del Conocimiento Del Dominio - GonzÃ¡lez Herrera, Manuel RamÃ³n; Santos, Yanet Garay; Ãlvarez HernÃ¡ndez, JuliÃ¡n Alberto (European Scientific Journal, ESJ, 2016)
The integration of Knowledge Engineering and Tourism strengthens the interdisciplinary studies as an area of scientific research. Therefore, the aim of this study is to compare the perceptions of different focus groups regarding the sustainability of tourism development in Ciudad Juarez, through conceptual modeling, specifically, using ontologies OWL derived from the Knowledge of the Domain in an Extended Lexicon. As results, theoretical approaches of tourism as a scientific discipline are systematized and interdisciplinary related to Knowledge Engineering. The tourism system of Ciudad Juarez is characterized, recognizing that it should be reoriented towards the formation of a Smart Tourist Destination, as an advanced concept in tourism. Finally, the knowledge apprehended by each focus group in relation to the tourism model is analyzed, in order to obtain a comparison between the four ontologies generated, and this concludes with the integration of perceptions in an OWL synthesis, which would guide the strategic projection of the destination.